Komunikasi Terapeutik Konselor Terhadap Anak Kekerasan Seksual Inses - Herawati, Zenna Puji (The Commercium, 2022)
Every year, the biological father is the most incest perpetrator in Indonesia, according Catatan Tahunan which released Komnas Perempuan in 2018. Indonesia still lacks incest regulation, making therapeutic is essensial. This study employs case studies and a descriptive qualitative method to learn about the therapeutic communication counselor process for trauma treatment. As a result, the counselor has 4 stages of communication : assesment, observation, performance, and termination.